IMPLEMENTASI PERENCANAAN TENAGA KERJA DAN SISTEM ALIH DAYA (OUTSOURCING) PADA PT. XYZ CABANG BANDUNG - Tamimah Manal Ayuningrum; Resya Dwi Marselina; Yulia Aryanti; Tasya Nuri Nurrohmani; Muhamad Fakhri Hamdi; Muhamad Dzikri A (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study analyzes the implementation of workforce planning and outsourcing systems at PT. XYZ Bandung Branch, with a focus on high employee turnover rate as the primary challenge. Using a descriptive qualitative method, data were collected through in-depth interviews with active area managers, a former area managers, and employees under other outsourcing companies in the Bandung region. The study also incorporated triangulation with academic literature and a review of labor regulations. The findings reveal that the company's workforce planning operates systematically through the utilization of Enterprise Resource Planning (ERP), talent management strategies, and a maximum position-filling policy within a seven-day timeframe. However, a critical gap was identified between procedural compliance and the normative protection of employee rights, particularly regarding the elimination of overtime compensation, which contradicts Article 27 of Government Regulation Number 35 of 2021. This gap, further compounded by a disproportionate supervisor-to-subordinate span of control and limited career advancement opportunities, positions the company within a low-road outsourcing model that structurally drives avoidable voluntary employee turnover. As a long-term solution, this study recommends a gradual transformation toward a high-road outsourcing model to ensure sustainable and competitive business operations.